2019
DOI: 10.1177/0333102419849013
|View full text |Cite
|
Sign up to set email alerts
|

The clinical spectrum of reversible cerebral vasoconstriction syndrome: The Italian Project on Stroke at Young Age (IPSYS)

Abstract: Introduction To describe clinical, neuroimaging, and laboratory features of a large cohort of Italian patients with reversible cerebral vasoconstriction syndrome. Methods In the setting of the multicenter Italian Project on Stroke at Young Age (IPSYS), we retrospectively enrolled patients with a diagnosis of definite reversible cerebral vasoconstriction syndrome according to the International Classification of Headache Disorders (ICHD)-3 beta criteria (6.7.3 Headache attributed to reversible cerebral vasoconst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 16 publications
4
30
1
Order By: Relevance
“…There is little evidence on the risk factors for complications. A previous analysis of our cohort found an association of female sex and migraine with hemorrhagic forms of RCVS [6] and several studies documented more complications in patients with secondary compared to idiopathic RCVS [3,7]. Singhal et al identified use of serotonergic antidepressants prior to RCVS and glucocorticoid treatment after onset of RCVS as risk factors for clinical and radiologic worsening [8].…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…There is little evidence on the risk factors for complications. A previous analysis of our cohort found an association of female sex and migraine with hemorrhagic forms of RCVS [6] and several studies documented more complications in patients with secondary compared to idiopathic RCVS [3,7]. Singhal et al identified use of serotonergic antidepressants prior to RCVS and glucocorticoid treatment after onset of RCVS as risk factors for clinical and radiologic worsening [8].…”
Section: Introductionmentioning
confidence: 66%
“…In our cohort, RCVS patients more often had complications than in the Japanese [16], Korean [7], and Taiwanese [2] cohorts, and less often than in an Italian [3] and two American cohorts [17,18]. Note: OR (95% CI) and p value from stepwise forward logistic regression including the variables thunderclap headache at onset, sex, migraine, postpartum, anxiety or depression, BP surge, and age.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The clinical spectrum of RCVS varies among different populations, and the diagnosis of atypical cases can be challenging. 21 Moreover, the classic "string of beads" appearance of vasoconstriction has been described in only 12%-81% of patients with RCVS. 4 Previous reports have suggested the benefit of calcium channel blockers (nicardipine, verapamil, and nimodipine) and phosphodiesterase inhibitors (milrinone) in diagnosing and treating RCVS (On-line Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…RCVS is a monophasic disease with a low recurrence rate and relapses are mostly benign [ 76 ]. Triggers as RCVS postpartum state, pre-eclampsia, recreational drugs, vasoactive substances, antidepressants, blood transfusions can be identified in some patients [ 77 ].…”
Section: Clinical Applicationsmentioning
confidence: 99%